Context-relevant strategies for ICT integration in teaching and learning science subjects in Tanzania secondary schools - Abdallah Ngodu; Placidius M. Ndibalema; Francis William (Academy of Cognitive and Natural Sciences, 2024)
Information and Communication Technology (ICT) can improve science teaching and learning. However, understanding the contexts in which ICT is intended to be integrated for its effectiveness is limited. Therefore, the current study explored context-relevant strategies and challenges for ICT integration in the teaching and learning science subjects in secondary schools in Tanzania. Exploratory sequential design under mixed methods guided the study's conduct. 52 participants (45 science teachers, six heads of schools and one municipal education officer) were purposefully and conveniently involved. Data were collected in two phases: 1st phase was qualitative data through in-depth interviews, 2nd phase was quantitative data through a questionnaire. Thematic analysis guided qualitative data analysis where MS Excel in the form of pivotal charts were used to present the frequency of the responses. SPSS version 27 guided the quantitative data analysis, presenting the output descriptively. Participants presented various context-relevant strategies, including capacity building for teachers, building and equipping computer labs with ICT facilities, maintaining and repairing defective computers, deploying educational technology experts, and making ICT compulsory at all levels of education. On the other hand, participants identified a lack of ICT facilities, limited ICT training opportunities, and digital content as context-relevant challenges for ICT integration in science teaching and learning. The study recommends rigorous pre-service and in-service teacher training programmes on ICT pedagogical integration for science teaching and learning based on these findings. Again, we recommend the improvement of ICT infrastructure in schools to enhance the availability, access, and use of science teaching and learning. The study concludes that if sufficient infrastructures are available and science teachers are equipped with ICT knowledge, teaching and learning of science subjects will be effective.